Acupuncture combined with antidepressants for mild-to-moderate depressive disorders: a systematic review with meta-analysis and trial sequential analysis - Wang, Yingdong; Yu, Yi; Zhang, Shike; Xi, Qiang; Qiu, Jiwen; Li, Xinju; Zhang, Mingxing; Guo, Yi (Frontiers in Neurology, 2025)
ObjectiveTo assess the synergistic effect of acupuncture combined with antidepressants in the treatment of mild-to-moderate depressive disorders.MethodsOur systematic search identified randomized controlled trials evaluating acupuncture combined with antidepressants for mild-to-moderate depression across eight databases, with records retrieved from each database’s establishment until October 29, 2025. Independent researchers critically reviewed the literature, recorded relevant data, and assessed the quality of research. Data were analyzed using RevMan 5.4, Stata 17.0, and TSA 0.9.5.10.ResultsThe study included a total of 975 patients across 15 trials. Meta-analysis revealed that compared with antidepressants alone, acupuncture combined with antidepressants could significantly improve patients’ HAMD-24 scores (MD = −1.43, 95% CI [−1.88, −0.98], p < 0.00001), HAMD-17 scores (MD = −2.80, 95% CI [−3.97, −1.62], p < 0.00001), early efficacy (MD = −2.00, 95% CI [−2.62, −1.38], p < 0.00001), total effective rate (MD = 2.44, 95% CI [1.65, 3.63], p < 0.00001), SDS scores (MD = −4.16, 95% CI [−5.70, −2.62], p < 0.00001), TESS scores (MD = −3.63, 95% CI [−5.50, −1.76], p = 0.0001) as well as the SERS scores (MD = −3.01, 95% CI [−3.79, −2.23], P<0.00001). Although there is publication bias in HAMD-24 and total effective rate, the trim-and-fill test has confirmed the robustness of the results. Trial sequential analysis (TSA) results demonstrated that acupuncture combined with antidepressants was significantly superior to antidepressants alone in improving HAMD-24 scores, HAMD-17 scores, early efficacy, total effective rate, SDS scores, TESS scores as well as the SERS scores. Moreover, TSA confirmed that the sample sizes for all outcomes were sufficient to support the robustness of these conclusions.ConclusionAcupuncture combined with antidepressants demonstrates a clear synergistic effect in treating mild to moderate depression. The combined therapy not only significantly outperformed antidepressants alone on primary efficacy endpoints but also demonstrated early therapeutic advantages as early as one week post-treatment, while markedly reducing medication-related side effects.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025641858, Identifier CRD42025641858.